2012
DOI: 10.1007/s11606-012-2268-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Record-Based Patient Identification and Individualized Mailed Outreach for Primary Cardiovascular Disease Prevention: A Cluster Randomized Trial

Abstract: BACKGROUND: Many individuals at higher risk for cardiovascular disease (CVD) do not receive recommended treatments. Prior interventions using personalized risk information to promote prevention did not test clinic-wide effectiveness. OBJECTIVE AND DESIGN: To perform a 9-month cluster-randomized trial, comparing a strategy of electronic health record-based identification of patients with increased CVD risk and individualized mailed outreach to usual care. PARTICIPANTS: Patients of participating physicians with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 25 publications
(28 reference statements)
0
54
0
Order By: Relevance
“…(24) In that trial, randomization to an individualized mailed CVD risk message intervention led to greater odds of receiving a lipid-lowering medication (OR 2.13, 95%CI 1.05-4.32). However, there are key differences between the two trials.…”
Section: Discussionmentioning
confidence: 99%
“…(24) In that trial, randomization to an individualized mailed CVD risk message intervention led to greater odds of receiving a lipid-lowering medication (OR 2.13, 95%CI 1.05-4.32). However, there are key differences between the two trials.…”
Section: Discussionmentioning
confidence: 99%
“…25 Several studies completed because this review have also demonstrated significant improvements in risk factor levels, and increased the use of preventive medication. 15,26,27 One difference between this study and most previous trials is that we used a pragmatic design with a waiver of informed consent that included all eligible patients receiving care at participating sites. Therefore, our findings may be more indicative of how this type of intervention performs in a general population rather than one limited to volunteer participants.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation for our observed findings is that this intervention led patients to discuss CVD prevention with clinicians but did not overcome some patients' reluctance to initiate drug therapy. The increase in patients who refused [12][13][14][15] and applies it to an entire population of patients receiving care in CHCs. Previous studies showed that providing individualized CVD risk information to patients has effects on patients' knowledge, attitudes, and some health behaviors, but the impact on CVD risk factors has been inconsistent, and the impact on health outcomes is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T his trial by Persell et al 1 tested an intervention that leveraged electronic health records to identify patients with risk factors for cardiovascular disease but not receiving statin treatment. The investigators provided a list of patients meeting these criteria to clinicians and mailed personalized letters to the patients on the list, offering advice regarding the benefit of statin treatment, controlling hypertension or quitting smoking.…”
mentioning
confidence: 99%